2003
DOI: 10.1007/s00431-003-1192-0
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for informed consent in biomedical research involving paediatric populations as research participants

Abstract: To promote and protect the best interests of children involved in biomedical research, paediatricians have to ensure that participating minors and their parents/legal representatives have understood and assented/consented to the research. Therefore guidelines providing child-specific guidance that are compatible with other international guidelines on informed consent are laid down. Special regard is paid to the willingness to participate and the social and cultural background of the patients, the legal conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 4 publications
0
21
1
1
Order By: Relevance
“…Although retrospective consent appears a contradiction in terms, it appears in several standards for performing emergency research, including the European guidelines for informed consent in biomedical research involving paediatric populations 30. While obtaining deferred or continuing consent in emergency situations seems intrinsically logical, the enrolment of participants in a study without explicit prior consent but using some form of ex post facto permission to satisfy inapplicable standards is logically incongruent.…”
Section: Paediatric Emergency Researchmentioning
confidence: 99%
“…Although retrospective consent appears a contradiction in terms, it appears in several standards for performing emergency research, including the European guidelines for informed consent in biomedical research involving paediatric populations 30. While obtaining deferred or continuing consent in emergency situations seems intrinsically logical, the enrolment of participants in a study without explicit prior consent but using some form of ex post facto permission to satisfy inapplicable standards is logically incongruent.…”
Section: Paediatric Emergency Researchmentioning
confidence: 99%
“…In most countries children younger than 16 years of age cannot legally consent to participate in research: their consent being delegated to their parents or legal guardian. [1][2][3] Generally, the informed consent is understood as informed parental permission and assent of the child. 1 4 The capability of children to give assent depends on age and relates to their cognitive, emotional, and social development; however, it has been suggested that factors such as general health status and anxiety about invasive procedures might play a role as well.…”
mentioning
confidence: 99%
“…It has been recommended that the content, the language, and the mode of communication should be adapted to assist the child to make an independent decision. 2 Assessment of possible effects of differentiated information procedures, however, has not been performed and little information, if any, on factors that may influence decision making in healthy children who are asked to participate in nontherapeutic research has been provided. The aims of the present study were to assess sociodemographic characteristics in healthy school children and adolescents who are invited to participate in non-therapeutic research, and to evaluate their motives for assent or dissent, and their understanding of age differentiated information.…”
mentioning
confidence: 99%
“…WHO does not support inducements to participate. [9] Challenges and Practicalities Of Obtaining Parental Consent And Child Assent In Paediatric Trials…”
Section: Obtaining Consent From Vulnerable Populationsmentioning
confidence: 99%